Microstructure and properties of Ni–Ti–Cu alloy fabricated in situ by treble-wire arc additive manufacturing - Peng Yu; Zhetao Liang; Xinya Chen; Hengsheng Ma; Mingfu Shao; Jian Han; Yinbao Tian (Virtual and Physical Prototyping, 2025)
Traditional manufacturing methods for Ti–Ni–Cu alloy are casting and powder metallurgy with the disadvantages such as high cost and long periods. In this study, Ti–Ni–Cu alloys are fabricated by treble-wire arc additive manufacturing (T-WAAM), a new technology with short periods, using pure Ti, pure Ni and pure Cu wires as raw materials. The results show that with an increase of Cu content from 5 at.% to 25 at.%, the phase transition temperature increases sharply from 30°C to 62°C. The ultimate tensile strength of Ti50Ni45Cu5, Ti50Ni35Cu15 and Ti50Ni25Cu25 is 248.2 ± 4.6 MPa, 534.8 ± 3.7 MPa and 261.8 ± 4.2 MPa, respectively. Their strain is 1.71 ± 0.31%, 6.42 ± 0.33% and 3.36 ± 0.37%, respectively. Their fracture mode is a brittle fracture. This study indicates that T-WAAM technology with in-situ alloying is feasible to fabricate the Ti–Ni–Cu alloys.